Pengembangan Media Pembelajaran Majalah Digital Flipbook Berbasis Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar IPA - Desy Nursafitri; Isa Ansori (Jurnal Penelitian Pendidikan IPA, 2024)
Science learning at SDS IT Nurul Yaqin in East Jakarta City is still monotonous. This is because the teacher uses a learning strategy that is centered on the teacher, which affects student learning outcomes and does not meet the KKTP that the school owns. One of the supporting variations in learning is by using interesting learning media and learning models. The purpose of this study was to develop, test the feasibility and test the effectiveness of digital learning media flipbook magazine on the learning outcomes of class V students of SDS IT Nurul Yaqin, East Jakarta City, especially on science material. The type of research is Research and Development (RnD) with the ADDIE model consisting of 5 stages. Documentation, interviews, questionnaires, and observations are all methods used for data collection. The results of the validation of learning media products by experts in material and media were 87.5% and 90% with a classification of "very feasible." The effectiveness with the T test was 0.000, and the NGain calculation results were 0.66 on a small scale and 0.60 on a large scale in the category of "moderate." Researchers suggest always developing digital learning models and media in order to create meaningful learning.